An insight into starch slowly digestible features enhanced by microwave treatment. (June 2020) - Li, Nannan; Wang, Lili; Zhao, Siming; Qiao, Dongling; Jia, Caihua; Niu, Meng; Lin, Qinlu; Zhang, Binjia
Abstract: The rice starch following microwave cooking with storage showed more slowly digestible starch and a lower digestion rate than did the conventionally treated counterpart. The underlying mechanism was interpreted by inspecting starch multi-level structural evolutions during digestion. Accompanying digestion, not only were starch matrices digested, leading to porous substrate and probably less polymorphs and nanoscale orders, but also starch chain reassembly occurred, causing A to B crystalline transform for untreated starch and formation of new molecular organization (repeat length: 5 nm) for treated starches. Hence, the digestion for native and treated starches was governed by concurrent matrix hydrolysis and molecular reassembly during digestion. The ultimate digestion of a specific structure was affected by the state of structural system. Unlike common views, the polymorphs in processed starches without native architecture were preferentially digested. Also, compared to conventionally treated counterpart, the microwave treated starch exhibited enhanced molecular reassembly during digestion, eventually displaying stronger slowly digestible features. Graphical abstract: Image 1 Highlights: Starch digestion was governed by concurrent matrix hydrolysis and chain reassembly. Polymorphs in processed starch could be preferentially digested. Microwave treated starch showed enhanced molecular reassembly during digestion.